Polyomavirus VP1 phosphorylation: coexpression with the VP2 capsid protein modulates VP1 phosphorylation in Sf9 insect cells. - Li, M (1995)
The polyomavirus virion has an outer capsid comprised of 72 pentamers of the VP1 protein associated with the minor virion proteins, VP2 and VP3, and the viral minichromosome. To investigate the interaction between VP1 and VP2/VP3, we mapped VP1 phosphorylation sites and assayed VP1 recognition by anti-peptide antibodies after coexpression of VP1 with VP2 or VP3 by using recombinant baculovirus vectors. VP1, expressed either alone or with VP3, was phosphorylated on serine residues, which are not modified during polyomavirus infection of mouse cells. When VP1 was coexpressed with VP2, the nonphysiologic serine phosphorylation of VP1 was decreased, and a tryptic peptide containing Thr-63, a site modified during virus infection of mouse cells, was phosphorylated. An anti-peptide antibody directed against the VP1 BC loop domain containing Thr-63 recognized VP1 expressed alone but not VP1 coexpressed with VP2 or VP3. The change in phosphorylation resulting from coexpression of two structural proteins identifies the potential of the baculovirus system for studying protein-protein interactions and defines a functional role for the VP1-VP2 interaction.